Efektivitas Penggunaan Media Pembelajaran Komputer Untuk Meningkatkan Hasil Belajar Mata Pelajaran TIK Kelas X SMAN 3 Makassar - Nofi Nafila; Ruslan; Mustari S. Lamada; Fadhilrrahman Baso (Sakura Digital Nusantara, 2025)
This study was conducted to assess the effectiveness of using learning media on the learning outcomes of ICT students in grade 10 at SMA Negeri 3 Makassar. A quasi-experimental research design with a pretest-posttest control group design was employed. The experimental group was class X.10, while the control group was class X.2. In the experimental class, learning was conducted using projector and PowerPoint media, while in the control class, conventional learning methods were used. Data collection techniques included tests for cognitive aspects and observations for psychomotor aspects. The study findings showed that (1) The independent sample t-test analysis of the posttest data yielded a t-count value of 0.311 with a significance of 0.05. This indicates that the significance (2-tailed) of 0.00 < 0.05, meaning the average score of the experimental class is different from that of the control class, with the experimental class having a higher average score. Additionally, the average N-Gain percentage of the experimental class was 91.21, categorized as very effective, while the control class had an average N-Gain of 45.16, categorized as less effective. (2) The observation data analysis showed that the experimental class had an average score of 68.95, while the control class had an average of 59.69. This indicates a difference in psychomotor learning outcomes between the experimental and control classes. Based on both data analyses, it can be concluded that the use of projector and PowerPoint learning media is effective in the ICT subject for grade X at SMA Negeri 3 Makassar, both in the cognitive and psychomotor aspects.are written in one paragraph consisting of 200 to 250 words. The abstract is a concise summary of the entire research paper and should include key elements such as background, research objectives, methods, results, and conclusions. The background should briefly describe the research problem and its significance. The research objective must be stated clearly. The methodology should be summarized to indicate how the study was conducted. The results should present the main findings, while the conclusion highlights the key takeaways and possible future research directions.